LEGALIZATION OF THE PRINCIPLES OF THE JUDICIARY IN AFRICAN CONSTITUTIONS: HUMANITARIAN AND STATE-INDUSTRY ASPECTS - Ivan N. Kuksin , Marina V. Markhgeym , Alevtina E. Novikova , Nina V. Stus , Aleksej P. Treskov (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The authors analyzed the principles of judicial power in the constitutions of African states. They showed that the modern constitutional development of African states is mediated by the history of the continent, as well as the ongoing political processes. The emergence of basic laws in these states has become the basis for both the establishment of constitutionalism and the establishment and functioning of key public authorities. According to the functional division of state power, the organization and activities of the judiciary are inherent. The source of such institutionalization and organization are constitutions. The analysis showed that the principles are formalized not only in the special structural parts of the constitutions, devoted to the court of various instances, but also in the humanitarian and state-industry sections.